A Comparison of Ground Penetrating Radar Profiles and Photographed Trenches, Sand Point, Michigan. - Tucker, Laura (My University, 2009)
The National Park headquarters of Pictured Rocks National Lakeshore is located at the tip of a cuspate foreland feature known as Sand Point. During high water levels of Lake Superior, coastal erosion and basement flooding have become a problem. The purpose of this project was to use hgih frequency (900 MHz) ground penetrating radar (GPR) data to provide detailed resolution of the subsurface.
Color poster with text and images.
Keywords: Pictured Rocks National Shoreline (Mich.); Sedimentation and deposition--Michigan--Pictured Rocks National Shoreline; Environmental mapping--Michigan--Pictured Rocks National Shoreline; Ground penetrating radar; Posters